2008
DOI: 10.1097/olq.0b013e31815abaef
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Human Papillomavirus Type 11 in the United States: Results From the Third National Health and Nutrition Examination Survey, 1991–1994

Abstract: This study represents the most comprehensive picture of HPV-11 infection in the United States to date, and provides baseline data on the prevalence of HPV-11 before availability of the quadrivalent HPV vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
5
13
3
Order By: Relevance
“…Behavioral factors associated with seropositivity in our study were similar to those reported elsewhere [15,16,39] and confirm data from prospective studies that lifetime number of sex partners is a strong predictor of HPV infection [8,40]. Although several factors were associated with seroprevalence in our bivariate analysis, among females in the multivariate model, only age, lifetime number of sex partners, and poverty level remained significant.…”
Section: Weighted Seroprevalence Of Any Human Papillomavirus (Hpv) supporting
confidence: 92%
See 2 more Smart Citations
“…Behavioral factors associated with seropositivity in our study were similar to those reported elsewhere [15,16,39] and confirm data from prospective studies that lifetime number of sex partners is a strong predictor of HPV infection [8,40]. Although several factors were associated with seroprevalence in our bivariate analysis, among females in the multivariate model, only age, lifetime number of sex partners, and poverty level remained significant.…”
Section: Weighted Seroprevalence Of Any Human Papillomavirus (Hpv) supporting
confidence: 92%
“…Other studies have described the HPV seroprevalence in the United States, but there has been no population-based study of all 4 HPV vaccine types [13][14][15][16]41]. Clinic-based studies have generally found a higher seropositivity than that revealed by our data.…”
Section: Weighted Seroprevalence Of Any Human Papillomavirus (Hpv) contrasting
confidence: 78%
See 1 more Smart Citation
“…The upward age trends associated with HPV 16 and 18 seroprevalences observed in this study are consistent with those reported in population-based (30), community-based (26, 42), or clinic-based studies (31, 3335). Only 3 studies have evaluated HPV 6 and/or 11 seroprevalence in men (27, 28, 31) and their findings on age have been mixed. The study of Hariri and colleagues showed a significant, increasing age trend for HPV 11 seroprevalence for males 6- to 49-year-olds, followed by an insignificant decline through age 59 in a population-based study of 3,589 men (28), similar to the age pattern observed for HPV 11 seroprevalence in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of HPV seropositivity in both sexes suggest that seroprevalence is lower among men than women [57] (see also reviews by Dunne et al [21] and Partridge et al [23] ). Possible reasons for this lower seroprevalence in men are speculative, but may include a greater proportion of transient infections or infections with lower viral load in men, or differences in the nature of the anatomic sites infected and immunologic response to infection [21,23] .…”
Section: Hpv Seroprevalencementioning
confidence: 99%